Operationalizing the State: Notes on Military Responses to Environmental Disasters - Tough, David (UnderCurrents: Journal of Critical Environmental Studies, 2006)
Over the past decade, Canadians have seen our armed forces increasingly deployed in response to environmental disasters. In 1996, the Saguenay River in eastern Quebec flooded, destroying homes in the region and bursting hydroelectric dams. In 1996 the Red River overflowed its banks, flooding large areas of central Manitoba; the largest Canadian military force deployed since the Korean War (8400 personnel) was sent in to contain the flood and deliver emergency supplies under Operation Assistance. In response to the Ice Storm in 1998, which left millions of Canadians in Quebec and eastern Ontario without power, the Department of National Defence launched Operation Recuperation, which it called “the largest deployment of troops ever to serve on Canadian soil in response to a natural disaster” (www.forcesgc.ca/site/operations/recuperation_e.asp). Climate change and the growing incidence of extreme weather mean we have most likely not seen the last of this new humanitarian role for the military.